Uncovering the Relationship between Corporate Social Responsibility (CSR), Fraudulent Financial Statements (FFS), and Culture: A Literature Review Study - Rizal Syafiie, Moh.; Herawaty, Netty; Mansur, Fitrini; Safelia, Nela; Kusumastuti, Ratih (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to examine the relationship between Corporate Social Responsibility (CSR), Fraudulent Financial Statements (FFS), and Culture through a Systematic Literature Review (SLR) approach. CSR is a form of corporate social responsibility that covers economic, social, and environmental aspects. At the same time, FFS is the manipulation of financial statements that aims to present information that does not match the actual conditions. The relationship between these two concepts is debated in the literature because although CSR is expected to increase transparency and accountability, cases of FFS are still common even in companies that claim to implement CSR well. Through the SLR method, this study collects and analyzes previous studies in the past five years to identify the relationship patterns and factors influencing CSR, FFS, and Culture. The results show uncertainty, with some studies supporting that CSR can reduce FFS risk through increased ethics and transparency. In contrast, other studies find that CSR can be used as a legitimization tool to hide manipulative practices. This research enriches the accounting and financial management literature by providing a more comprehensive understanding of the role of CSR in FFS control and its practical implications for firms and stakeholders.